Connecting Silent Worlds: Requirements for Automatic Oral-Sign Language Translation - Santos, Natália Sales; Souza, Lucas Almeida S. de; Soares, Julia Manuela G.; Prates, Raquel Oliveira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
One of the challenges deaf people face when trying to access to health services is communicating with health professionals. These communication difficulties can result in health risks, such as diagnostic and treatment errors. To overcome such difficulties, it is essential to develop automatic translation systems that facilitate interaction between deaf people and healthcare professionals. The work presented in this article is inserted in the context of the project “Captar-Libras: Video communication system for the deaf applied to pre-medical care” (In Portuguese:“Captar-Libras: Sistema de Comunicação por vídeos para surdos aplicado ao pré-atendimento médico”), which aims to generate a bidirectional Portuguese-Libras translation through the use of photorealistic avatars for healthcare. This study presents a set of requirements that aim to guide the development of these systems. These requirements consider the specific needs of both deaf people and healthcare professionals.